2015
DOI: 10.1038/srep16877
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi P21: a potential novel target for chagasic cardiomyopathy therapy

Abstract: Chagas disease, which is caused by the parasite Trypanosoma cruzi, is an important cause of cardiomyopathy in Latin America. It is estimated that 10%–30% of all infected individuals will acquire chronic chagasic cardiomyopathy (CCC). The etiology of CCC is multifactorial and involves parasite genotype, host genetic polymorphisms, immune response, signaling pathways and autoimmune progression. Herein we verified the impact of the recombinant form of P21 (rP21), a secreted T. cruzi protein involved in host cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
19

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 56 publications
0
17
0
19
Order By: Relevance
“…Our previous studies showed that a murine endothelial cell line (tEnd) treated with different concentrations of rP21 did not exhibit altered cell viability or adhesion to a thin layer of extracellular matrix, but vessel formation was inhibited after 18 hours of incubation15. However, an intriguing question was raised: how does P21, a parasite-derived molecule, significantly interfere with the angiogenesis process?…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies showed that a murine endothelial cell line (tEnd) treated with different concentrations of rP21 did not exhibit altered cell viability or adhesion to a thin layer of extracellular matrix, but vessel formation was inhibited after 18 hours of incubation15. However, an intriguing question was raised: how does P21, a parasite-derived molecule, significantly interfere with the angiogenesis process?…”
Section: Resultsmentioning
confidence: 99%
“…This protein binds to CXCR-4 receptor (Silva et al, 2009; Rodrigues et al, 2012), recruits immune cells, induces IL-4 production, and decreases blood vessels formation. This protein can be a potential target for developing novel treatment against chagasic cardiomyophaty (Teixeira et al, 2015). …”
Section: Invasion Mechanism Of Trypanosoma Cruzimentioning
confidence: 99%
“…Enquanto isso, o tratamento com inibidores de óxido nítrico resulta em aumento da parasitemia e da taxa de mortalidade dos camundongos infectados (VESPA et al, 1994;PETRAY et al, 1995). Em relação ao aumento de IL-4 induzido por rP21, tal resultado corrobora com o visto em modelos de implantes de esponja in vivo desprovidos de infecção (TEIXEIRA et al, 2015). 2011;SAMUDI et al, 1998;DE MORAIS et al, 2015).…”
Section: Rp21 Aumenta a Polimerização Do Citoesqueleto De Actina Em Cunclassified
“…Análises mostraram que o tratamento com a proteína recombinante promoveu inibição da proliferação celular e a maior expressão de fatores antiangiogênicos, como sFlt-1 e menor expressão de VEGFA, molécula com atividade pró-angiogênica (TEIXEIRA et al, 2017 Estudos in vitro e in vivo tem demonstrado a presença de mastócitos associados à infecção cardíaca por T. cruzi (ALMEIDA, PEREIRA, TAFURI, 1975;POSTAN, CORREA, FERRANS, TARLETON, 1994;MEUSER-BATISTA et al, 2008). No presente estudo, realizamos a contagem de mastócitos totais, granulados e degranulados no tecido cardíaco dos animais e observamos que a presença dos mastócitos totais e degranulados foi significativamente menor no grupo infectado com 10 Mastócitos têm sido relacionados com a presença de disfunções cardiovasculares, como doença isquêmica cardíaca, infarto experimental do miocárdio, miocardite e insuficiência cardíaca (PALLADINI, TOZZI, PERLINI, 2003;FRANCIS & TANG, 2005;MARTIN et al, 1993;BROWEI & JANICKI, 2005;TEIXEIRA et al, 2015). Tafuri e Raso (1983) (KALESNIKOFF E GALLI, 2008;FARAHANI et al 2010;OVERED-SAYER et al, 2014;VILELA, 2015).…”
Section: A Proteína P21 Recombinante Diminui O Dano Cardíaco Preservunclassified
See 1 more Smart Citation